On (J,pn) summability of Fourier series - S. M. Mazhar (International Journal of Mathematics and Mathematical Sciences)
In this note two theorems have been established. The first one deals with the summability (J,pn) of a Fourier series while the second on concerns with the summability of the first derived Fourier series. These results include, as a special case, certain results of Nanda [1].